POTRET KEHIDUPAN KOMUNITAS PUNK (STUDI KASUS ANAK PUNK DI LAPANGAN SAMBER KOTA METRO) - Hamdi Abdul Karim (INSTITUT AGAMA ISLAM NEGERI METRO, 2021)
The research objective: The portrait of the life of the punk community (a case study of punk children in the samber field of Metro City) is to describe the family, socio-cultural and religious life of the punk community in the samber field of Metro city. This research is a qualitative study using a descriptive approach as the main frame of mind. In this study, observation, interviews and documentation as data collection methods. The informants of this research were punk kids who were in the samber field in Metro city. The results of the research, researchers found that there were characteristics of punk children from the community in the samber field when viewed from the way they appeared. Nan not all punk kids in the samber field understand the symbols of the clothes and appearance symbols they use. The punk kid who was in the samber field in Metro City was also from outside the Metro. The motivation for children to enter the punk community is to seek a free life without being regulated by inherent norms and restrain individuals. In addition, there are also those who join the punk community because of the condition of a broken home family, The role of the family is very important in shaping a child's personality. Then the socio-cultural conditions and the condition of a superficial understanding of religion in a person can also influence it.